Scale Development of the Panic Buying Tendency - Prissianingsih, P; Husna, Aftina Nurul (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2023)
This article presents efforts to develop the Panic Buying Tendency psychological scale. This scale trial aims to develop a psychological scale that measures how much or the level of panic buying tendencies in the subject community of this study totaling 110 general public aged over 18 years with the data collection method using a questionnaire made using Googleform and printed booklets. This research was conducted in 4 stages: determining the measurement area, writing items, testing the scale, and psychometric analysis. The reliability test was carried out by referring to the V Aiken's formula (v ? 0.80) and the reliability test used the Alpha Cronbach internal consistency method (r> 0.30). based on the scale trial, a Cronbach alpha value of 0.934 was obtained with a final item of 20, consisting of 10 favorable items and 10 unfavorable items. This scale aims to find out how big or the level of panic buying tendency in the community when buying necessities.